2011
DOI: 10.3109/00365599.2011.621142
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of nephrogenic systemic fibrosis at a large university hospital in Sweden

Abstract: Objective. Nephrogenic systemic fibrosis (NSF) is a rare condition that may follow administration of gadolinium-based contrast media (Gd-CM) in patients with renal insufficiency. This study was initiated to determine the incidence of NSF at Skåne University Hospital, Malmö, in Sweden. Material and methods. During the period January 2001 to December 2008 10 650 patients underwent magnetic resonance imaging (MRI) examinations. The re-expressed four-variable Modification of Diet in Renal Disease (MDRD) equation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Characteristics of included studies are provided in Table 1 . Studies were published from May 2008 through April 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of included studies are provided in Table 1 . Studies were published from May 2008 through April 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating literature and newer guidelines have recognized that not all GBCAs have the same risk of NSF. The American College of Radiology (ACR) manual on contrast media, version 10.3 and the European Society of Urogenital Radiology guidelines on contrast agents, version 10.0 recognize differences in risk of NSF between GBCAs and classify GBCAs into 3 distinct (albeit slightly different) groups .…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study from Sweden, no NSF patients were found when the NSF diagnosis was searched for among 272 patients with renal insufficiency exposed to GBCA [34]. However, no clinical examinations were performed either.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects a culture shift highlighted by a recent report of widely adopted policy changes among nephrologists across the USA relating to Gd contrast use in renal impairment and awareness of the risk factors and morbidity associated with NSF [62]. Since 2007, there has been a dramatic drop in the number of NSF cases reported, with multiple large studies in Sweden and the USA identifying reduced incidence or no new cases of NSF following restrictive prescribing policies [42,44,59,63]. In particular, no new pediatric cases of NSF have been reported to the Yale Registry in the period 2007-2013 (personal communication, Yale NSF Registry).…”
Section: Published Guidelinesmentioning
confidence: 99%